Early vs. late rate of torque development: Relation with maximal strength and influencing factors - Cossich, V.; Maffiuletti, N. A. (Journal of Electromyography and Kinesiology, 2020)
We re-examined the relationship between rate of torque development (RTD) and maximal voluntary contractions (MVC) torque, and investigated some possible neuromuscular determinants of early (=100 ms) and late (=200 ms) RTD. Seventeen healthy men performed maximal explosive isometric knee extensions at five joint angles, from which MVC torque, RTD at different time intervals (50-250 ms), and early quadriceps EMG activity (EMG50) were evaluated. Quadriceps muscle thickness (MT) was quantified by longitudinal ultrasonography. The relationship between MVC torque, EMG50 and MT against RTD was assessed with Pearson`s and repeated measures correlation coefficients. Moderate-to-strong correlation coefficients were observed between MVC torque and RTD (r = 0.50-0.88, p < 0.001), with stronger relationships for late RTD than for early RTD. Weak-to-strong correlation coefficients were observed amongst RTD and EMG50 (r = 0.37-0.83, p < 0.001), with stronger relationships for early RTD than for late RTD. Only late RTD was significantly correlated with MT, though only moderately (r = 0.50-0.52, p < 0.05). These findings suggest that early and late knee extension RTD are potentially governed by different neuromuscular factors. Neuromuscular activation seems to have a greater influence on early RTD than on late RTD, and vice versa for muscle mass.